A General Framework for Open Service Innovation in Logistics - Katharina Kalogerakis; Nikolaus Wagenstetter (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Compared to other industries the innovative output of logistics service providers (LSPs) is rather low. By enforcing their attempts to innovate these companies could improve their competitive position. Empirical studies indicate that proactive innovations result in significant improvements of customer loyalty for LSPs. Most LSPs are B2B service providers and therefore depend heavily on good relationships with their customers. Additionally, they have to act in a very competitive environment characterized by low profit margins. Looking at this special position, the question arises if methods of open innovation are a suitable approach for LSPs to fix their innovation deficit. Methods of open innovation originate from development processes of tangible products. Although, by now, open service innovation is also evolving, the logistics sector is still lacking behind. The aim of this paper is to evaluate a general framework for open service innovation in logistics. To specify requirements of LSPs in regard to open innovation procedures, interviews with responsible managers of LSPs were conducted.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; open innovation; logistics service providers; innovation methods; interviews